The Overview of Political Science in Contemporary Politics - Harryanto Aryodiguno (President University, 2023)
In this article, the author discusses the concepts of nations and states, power and authority. They examine the different ways in which nations and states can combine and the various forms of power and influence that can be exerted. The author also touches on how power can be used to shape preferences and control the climate of opinion. The article concludes by noting that awareness of the different forms of power and how they are exercised is important in understanding the dynamics of political systems.